Using Measurement Invariance to Explore the Source of Variation in Basic Medical Science Students’ Evaluation of Teaching Effectiveness - Alquraan, Mahmoud; Alazzam, Sulaf; Alkhateeb, Hakam (International Journal of Statistics in Medical Research, 2023)
Introduction: Many research studies have shown that students' evaluations of teaching(SET) are affected by different variables without testing the requirement of fair comparisons. These studies have not tested the measurement equivalency of SET surveys according to these variables. Measurement equivalency of SET refers to whether a SET survey is interpreted similarly across different groups of individuals (Variable Levels). Without evidence of measurement invariance across different variables under investigation, the SET ratings should not be compared across these variables and this is the goal of this study. Methods: Measurement Invariance analysis of SET survey was investigated using 1649 responses to SET of four different medical core courses offered by the College of Science and College of Medicine and from different levels. Results: The results showed the existence of teaching practices in the SET survey that are not equivalently loaded on its factor across the levels of targeted variables, and the college offered medical courses were a source of variation in basic medical science students’ evaluation of teaching effectiveness. On the other hand, teaching practices in the SET survey are equivalently loaded on its factor across course levels. Discussion: The study results showed that the SET of medical courses is comparable to the courses only taught by the College of Medicine. These results provide evidence that medical courses are different from other courses offered by other colleges. This means that comparing SET of the College of Medicine with other colleges and colleges of medicine needs to compare SET results at the college level only.